Nanopartículas de prata como plataforma de sensoriamento na detecção de arsênio inorgânico por espectrofotometria UV-Vis em amostras de arroz e camarão - Lima, Francisco Eduardo Holanda (2022)
Significant levels of arsenic (As) have been reported in rice and seafood samples. As a result, simple and low-cost methods for the analysis of arsenic speciation have been sought, as different forms of arsenic have varying levels of toxicity, with inorganic species being the most harmful to food safety. Therefore, recent studies have reported the use of silver nanoparticles as optical nanosensors for the quantification of this contaminant. In this study, a methodology for the synthesis of silver nanoparticles (AgNPs) functionalized with polyethylene glycol (PEG200) was investigated for their subsequent application as a sensing platform for the detection and speciation analysis of inorganic arsenic (iAs) in rice and shrimp samples using UV-Vis molecular absorption spectroscopy. The method was based on the phenomenon in which the presence of iAs in the medium shifts the plasmonic band exhibited by the AgNPs from 412 nm to 600 nm, enabling the analysis of iAs through spectroscopic measurements. The synthesized nanomaterial was characterized through surface charge and particle size measurements using Zeta potential and Dynamic Light Scattering (DLS), respectively. The results obtained suggest that the particles have a negative surface charge, while their size ranges from 80-100 nm. The AgNPs/UV-Vis spectrophotometry analysis method was efficient for the analysis of total arsenic (tAs) in rice samples with recoveries of 97% and 95% in the analysis of Reference Material - Agro C1001a and NIST 1568b - Rice Flour, respectively. In addition to being selective for iAs, allowing for accurate arsenic speciation (105% recovery of iAs in NIST 1568b - Rice Flour). The proposed method exhibited good precision with RSD (Relative Standard Deviation) less than 16% for all samples, and detection and quantification limits of 0.656 μg kg-1 iAs and 1.988 μg kg-1 iAs, respectively. The rice samples showed tAs levels ranging from 108.3 to 281.25 μg kg-1, which are below the limits recommended by Brazilian legislation for this type of matrix. The iAs content in the rice samples ranged from 55.35 to 110.02 μg kg-1, corresponding to 34-70% of the total As content. The concentration of iAs found in the shrimp sample was 64.70 μg kg-1. The present analysis method proved to be a viable and simple alternative for the analysis of iAs in rice and shrimp, highlighting its versatility for different matrices, plant, and animal tissues.